Partially Reduced Holey Graphene Oxide as High Performance Anode for Sodium‐Ion Batteries. Issue 7 (27th December 2018) - Zhao, Jin; Zhang, Yi‐Zhou; Zhang, Fan; Liang, Hanfeng; Ming, Fangwang; Alshareef, Husam N.; Gao, Zhiqiang
Abstract: The current Na + storage performance of carbon‐based materials is still hindered by the sluggish Na + ion transfer kinetics and low capacity. Graphene and its derivatives have been widely investigated as electrode materials in energy storage and conversion systems. However, as anode materials for sodium‐ion batteries (SIBs), the severe π–π restacking of graphene sheets usually results in compact structure with a small interlayer distance and a long ion transfer distance, thus leading to low capacity and poor rate capability. Herein, partially reduced holey graphene oxide is prepared by simple H2 O2 treatment and subsequent low temperature reduction of graphene oxide, leading to large interlayer distance (0.434 nm), fast ion transport, and larger Na + storage space. The partially remaining oxygenous groups can also contribute to the capacity by redox reaction. As anode material for SIBs, the optimized electrode delivers high reversible capacity, high rate capability (365 and 131 mAh g −1 at 0.1 and 10 A g −1, respectively), and good cycling performance (163 mAh g −1 after 3000 cycles at a current density of 2 A g −1 ), which is among the best reported performances for carbon‐based SIB anodes. Abstract : Partially reduced holey graphene oxide is prepared by low temperature reduction of holey graphene oxide. The large interlayer distance, short ion transfer distance, increased ion insertion/extraction sites, and residual oxygenous groups endow partially reduced holey graphene oxide with high sodium ion storage capability. This approach provides a facile and scalable strategy to produce high‐performance anode materials for sodium ion batteries.